A Cross-Cultural Study of American and Russian Proprieties in Communication - Oxsana S Issers; Sandra Halvorson (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2015)
An examination of eleven intercultural textbooks, used in the field of communication in America, reveals little research comparing Russian and American proprieties in communication (Chen & Starosta, 1998; Dodd, 1998; Jandt, 2004a; Jandt, 2004b; Kelly, Laffoon & McKerrow, 1994; Lustig & Koester, 1996; Martin & Nakayama, 2004; Martin & Nakayama, 2005; Martin, Nakayama & Flores, 2002; Samovar & Porter, 2003; Samovar & Porter, 2001). In order to investigate the similarities and differences (S/D) of the two countries, an instrument was developed containing questions dealing with proprieties and customs appropriate in both cultural settings. In order to maintain language integrity, the 29-item instrument was administered to English speaking students with: 1) no direct exposure to the Russian culture, or 2) direct exposure to the Russian culture. The results suggest proprieties in American and Russian society are more similar than difference in the majority of areas investigated in this research. However, there was a substantial difference between the two cultures in the following four areas: a) Russians are less likely than Americans to discuss their ethnicity in public situations; b) Russians are more polite than Americans in social situations; c) Russians feel more comfortable than Americans about speaking their minds in public situations; d) Russians are more honest when expressing opinions than their American counterparts.